BIOMODE : Biomechanical Modeling of Deglutition. (2019)
Deglutition or swallowing is the process in which, coordinate motion of several muscles transport the food bolus, from the oral cavity to the low esophageal sphincter. This process is composed by several stages such as food bolus preparation, propulsion, pharyngeal and esophageal stages. In general, any physiological or pathological affection to this coordinated process is known as dysphagia, and it is associated with stroke survivors, Parkinson, multiple sclerosis, and in general aged related diseases. Dysphagia severely affects the life quality of the patient and can cause death, mainly to the effects of food bolus aspiration (aspiration pneumonia). This research was done in collaboration with GIPSA-LAB, who work under the macro project “eSwallHoome”, funded by the French Agence Nationale de la Recherche (FANR) The research has as the main objective to study and explain the mechanisms of breathing and swallowing via in vivo, in vitro and in simulacra approaches. The project Biomechanical modeling of deglutition (Biomode) is focused on modeling the behavior of food bolus during the swallowing process. This project aimed to contribute to the understanding of the physical phenomena underlying swallowing. Particularly, this project developed tongue’s elastic models and simplified models related with the interaction of a liquid, Newtonian food bolus and the oral cavity during the oral propulsion stage. The approach of the study was both experimental and computational. The highlights of the project included: 1. Mechanical models of tongue’s motion and deformation based on hyperelastic muscle’s properties. 2. Numerical tools for the simulation of large displacement models coupled with nonlinear elastic materials that would potentially describe the fluid structure interaction during oral propulsion stage and also compare the results with experimental data taken from a simplified bench and 3. Generation of simplified dimensionless models of oral propulsion stage based on the interaction between a Newtonian fluid food bolus and the physiological accurate tongue’s dynamics, responsible for oral propulsion. During the project, GIPSA-Lab/TIMC-IMAG laboratories from Grenoble and Nicolas Hermant from Universidad del Valle, developed a full 3D nonlinear elastic model using finite element method and high displacement models of human tongue biomechanics. Also, a basic fluid structure interaction with Newtonian fluid and a nonlinear latex membrane with high displacement model was implemented in ANSYS® Workbench. Finally, two novel simplified dimensionless models for estimation of fluid/tongue interaction load as function of flow regime and fluid food bolus properties were proposed.